Metodologia para localização e dimensionamento de pequenas fontes de geração distribuída em redes de distribuição a partir de uma análise multicriterial - Canha, Luciane Neves (2004)
In the last years the distributed generation (DG) has been the objective of researches in many countries. This generation type presents advantages in relation to centralized generation, such as the reduction of technical losses, efficient uses of co generation and positive influence on the quality of the supplied energy. These advantages appear alon g the development of the methodology presented in this Thesis for dimensioning and location of small distributed generation sources in the distribution system beginning with multicriteria decision making. Also the influence of the DG on the distribution sy stem is analyzed over their operational characteristics. The methodology takes into account configuration, parameters and typical operational conditions of the Brazilian distribution systems. The developed algorithms are presented for determination of the power and operational characteristics of DG sources that are necessary to satisfy pre established criteria. Furthermore, it proposed a method to locate the sources in the distribution system, taking into account multiples criteria. For this reason, the app roach of Bellman Zadeh was used because it allows to include, besides the quantitative criteria that characterizes the power and energy losses, initial investment and operational cost, the qualitative criteria, like operational safety, co generation possib ility and readiness of physical space of the facilities. As an example of DG source the fuel cells were chosen by their low temperature for a promising electric and thermal source of energy. In the sequence, this Thesis presents models for estimate technic al losses including the influence of the DG sources. It also presented an analysis of the impact of the DG sources on the voltage levels of distribution systems. With that is possible to decide for the alteration of the taps of distribution transformers an d of the consequent control law of the substation voltage, in a way to guarantee the quality improvement of the energy supplied with the installation of GD. Practical verification of the developed theory is accomplished through experimental calculations on data of local Companies whose results and conclusions are presented in the final chapters.